Destination Management Organization (DMO): Paradigma Baru Pengelolaan Pariwisata Daerah Berbasis Teknologi Informasi - Prakoso Bhairawa Putera; Sri Mulatsih; Sri Rahayu (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
Now days, e-tourism, a part of the face of the development in tourism sector, begins to turn into newparadigm in management system which strongly needs more interactive information technology (IT). Within thisparadigm, stakeholders of tourism sector in one region usually enhance the e-tourism with providing a solidtourism management through a system called Destination Management Organization (DMO). Based on thiscondition, this paper aims to analyze the framework of this new system which has been adopted in some regionsin Indonesia. Using explorative analysis method, this paper finds that DMO in those regions basically stilldepends on the coordination tourism stakeholders, destination crisis management and destination marketingKata Kunci: e-tourism, new paradigm, ict, dmo